Evaluation of maternal and fetal outcome in patients of abruptio placentae in a tertiary care center, Kolkata: A descriptive and observational study - Sarmistha Barua; Aparna Chakrabarty; Amrita Samanta; Animesh Naskar (Asian Journal of Medical Sciences, 2022)
Background: Placental abruption (PA) contributes almost 30% of the all cases of antepartum hemorrhages. Both mother and fetus are at huge risk of maternal and neonatal morbidity and mortality when mother is complicated by this obstetric condition. Aims and Objectives: The aim of this study is to find out the incidence and the fetomaternal outcome in the patients of abruption placenta. Materials and Methods: A descriptive and observational study was conducted in the Department of Obstetrics and Gynaecology, in a tertiary teaching hospital in Kolkata, between January 01, 2018 and July 31, 2019, after obtaining ethical approval from the Institutional Ethics and Review Committee of R G Kar Medical College (reference number: RKC/Ethics/05). By convenience sampling method, we included 114 cases with gestational age of 28 completed weeks or more and diagnosed to have abruption placenta either clinically and/or ultrasonically. Statistical Package for the Social Science version 20 was used for analysis. Point estimate at 95% confidence interval was calculated along with frequency, percentage, mean, and standard deviation. Results: The mean age of mothers was 25.19±5.56 years. The incidence of PA was found to be 0.99% (1.18–0.8154 at 95% confidence interval) among deliveries conducted in this hospital. The majority of women 78 (68.42%) were mixed type and 57 (50%) found at 36 weeks or more gestational age. Most common presentations were vaginal bleeding 108 (94.74%) followed by pain abdomen 74 (64.91%). Most women 103 (90.35%) underwent cesarean section. Postpartum hemorrhage occurred in 10.53% and 73.68% cases needed blood transfusion. Fetal outcome included preterm (50%) and neonatal intensive care admission (24.56%), still born 6.14%. Conclusions: PA is unpredictable and not preventable but morbidity and mortality can be reduced by adequate antenatal care, early detection and monitoring of risk factors, improved nutrition status and multidisciplinary management and timely admission with facilities of neonatal intensive care unit support.